2018
DOI: 10.1111/jace.16257
|View full text |Cite
|
Sign up to set email alerts
|

Solution electrowriting of highly stable TiN nanofiber pattern for transparent electrode under extreme environment

Abstract: The fast developing electronic industry boosts higher demand of transparent electrode. Nanofiber network design provides a new platform for finding alternative materials to replace the traditional indium-doped tin oxide (ITO) film as transparent electrode. In this work, the TiN nanofiber network with a micron-scale precise geometry was firstly assembled by solution electrowriting. Unlike the ordinary opaque TiN film or bulk, the geometry patterned TiN nanofiber network achieved an ultrahigh transparency above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…It is evident that at low collector speeds the filaments are deposited randomly on the collector plate. The increase in collector speed reduced that randomness until a critical translational speed (CTS) was achieved (a common process reported in previous studies 57 ) which was 14 mm/s in this case. Beyond this speed excessive breakages of deposited filaments started because of the unnecessary draft (drawing effect) of the filaments.…”
Section: Effect Of Collector Speedsupporting
confidence: 62%
“…It is evident that at low collector speeds the filaments are deposited randomly on the collector plate. The increase in collector speed reduced that randomness until a critical translational speed (CTS) was achieved (a common process reported in previous studies 57 ) which was 14 mm/s in this case. Beyond this speed excessive breakages of deposited filaments started because of the unnecessary draft (drawing effect) of the filaments.…”
Section: Effect Of Collector Speedsupporting
confidence: 62%
“…A comparison of FOM values with ten previous representative studies is shown in Figure 3d. [ 70–77 ] The MGZO TE shows excellent FOM values, and, despite comprising a single film with an inexpensive constitution compared to the previously reported materials, it exhibits the best optoelectronic properties. A comparison between other studies reported far is provided in Table S2, Supporting Information; the FOM, known as the “Haacke FOM” ( Φ H ), is also listed.…”
Section: Resultsmentioning
confidence: 99%
“…Although silver, copper and other metal NFs have the advantages of low sheet resistance, high transmittance and moderate flexibility, they have high chemical activity and are easy to be oxidized or chemically corroded [185]. This instability seriously affects its performance and service life.…”
Section: Uniform Mixed Materialsmentioning
confidence: 99%